Optimization of Progressive Freezing on Synthetic Produced Water by Circular Moving Cylindrical Crystallizer via Response Surface Methodology - Wan Nur Athirah Mazli; Shafirah Samsuri; Nurul Aini Amran; Eduard Hernández Yáñez (Crystals, 2021)
Treatment and disposal are two main approaches for water cycle management in the oil and gas industry. Freeze concentration has been identified as one of the methods to separate water from wastewater samples. The conventional method used for solution movement in progressive freezing technique is stirring by a stirrer. However, the stirrer requires frequent maintenance as it needs to be cleaned and requires longer cleaning time due to the complex structure of a stirrer. Thus, the new solution movement for progressive freezing is proposed, which is circular moving progressive freezing. This study aims to remove water from the wastewater sample (i.e., produced water). To optimize and investigate the effect of coolant temperature, freezing time and rotation speed, response surface methodology (RSM) was applied to determine the efficiency of the process and central composite design (CCD) was used to design the experiment. From the results, the optimum parameters were determined at the freezing time of 22.79 min, coolant temperature of −14.89 °C and rotation speed of 59 rpm. To evaluate the accuracy of the optimization process, a validation experiment was performed and water removal value of 89.67% was achieved.